Transplantation: platform to study recurrence of disease - Burke, George William; Mitrofanova, Alla; Fontanella, Antonio Miguel; Vendrame, Francesco; Ciancio, Gaetano; Vianna, Rodrigo M.; Roth, David; Ruiz, Phillip; Abitbol, Carolyn L.; Chandar, Jayanthi; Merscher, Sandra; Pugliese, Alberto; et al. (Frontiers in Immunology, 2024)
Beyond the direct benefit that a transplanted organ provides to an individual recipient, the study of the transplant process has the potential to create a better understanding of the pathogenesis, etiology, progression and possible therapy for recurrence of disease after transplantation while at the same time providing insight into the original disease. Specific examples of this include: 1) recurrence of focal segmental glomerulosclerosis (FSGS) after kidney transplantation, 2) recurrent autoimmunity after pancreas transplantation, and 3) recurrence of disease after orthotopic liver transplantation (OLT) for cirrhosis related to progressive steatosis secondary to jejuno-ileal bypass (JIB) surgery. Our team has been studying these phenomena and their immunologic underpinnings, and we suggest that expanding the concept to other pathologic processes and/or transplanted organs that harbor the risk for recurrent disease may provide novel insight into the pathogenesis of a host of other disease processes that lead to organ failure.